Obtenção de cerâmicas à base de tricálcio fosfatos utilizando óxido de manganês como aditivo - Ramalho, Eduardo Galvão (2006)
The calcium phosphate ceramics have been very investigated as material for bone implants. The tricalcium phosphate (β-TCP) had a great potential for application in temporary implants like a resorbable bioceramic. This material presents a limitation in its sintering temperature due to occurrence of the allotropic transformation β → α at temperatures around 1200°C, not allowing the attainment of dense ceramic bodies. This transformation also causes cracks, what diminishes the mechanical strength, limiting its use to applications of low mechanical requests. This work studies the influence of the addition of manganese oxide in the sintering of β-TCP. Two processing routes were investigated. The first was the powder metallurgy conventional process. The test bodies (samples) were pressed and sintering at temperatures of 1200 and 1250°C. The second route was uniaxial hot pressing and its objective was to obtain samples with high relative density. The samples were physically characterized through density and porosity measurements. The thermal behavior was studied through dilatometric, thermal differential and thermogravimetric analysis. The mechanical properties were characterized by three point flexure test and Vickers microhardness measurements. The microstructure was analyzed by scanning electron microscopy. The addition of manganese oxide caused an improvement of the mechanical strength in relation to the material without additive and promoting the stabilization of β-TCP to greater temperatures